'Red is the colour of the heart': making young children's multilingualism visible through language portraits. (20th October 2020) - Soares, Camila Tabaro; Duarte, Joana; Günther-van der Meij, Mirjam
Abstract: The increasing occurrence of multilingualism in the educational sphere is challenging teachers to deal with the coexistence of different languages in the classroom. The present paper presents the analysis of language portraits as a tool to make students' multilingualism visible by using colours to represent their multilingual repertoires. Through a mixed methods design, our research analyses 570 language portraits and sociolinguistic surveys, as well as 21 semi-structured interviews with children aged 6 to 13 in order to investigate the ways in which pupils represent and reflect upon their multilingual repertoires. Using a qualitative content analysis, we have classified the most common patterns within pupils' choices of colours and placement of languages on their portraits, later analysed through a semiotic approach. Results show three recurring patterns of colour choices: colours of national flags, associations with life experiences, and associations with feelings. As for language placement, results show two recurring patterns: structuring languages according to linguistic skills, and according to body functions. The analysis also revealed a tendency among participants of representing their languages through a "monolingual lens" (García and Flores) and draws implications for the implementation of multilingual education.